Rifle Shooting for Athletes With Vision Impairment: Does One Class Fit All? - Allen, Peter M.; Latham, Keziah; Ravensbergen, Rianne H. J. C.; Myint, Joy; Mann, David L. (Frontiers in Psychology, 2019)
Revised evidence-based classification criteria introduced for shooting for athletes with vision impairment (VI shooting) suggest that athletes with impaired contrast sensitivity (CS) and visual acuity (VA) should be eligible for inclusion in the sport but should all eligible athletes compete against each other in the same “class” or is more than one class necessary? Twenty-five elite VI shooting athletes took part in the study. Two measures of visual function were assessed under standardized conditions: VA (using an ETDRS logMAR letter chart, and/or a BRVT chart) and CS (using both a Pelli-Robson chart and a Mars number chart). Shooting performance, in both prone and standing events, was measured during an international VI shooting competition. Fourteen of the 25 athletes had measurable VA, and for CS, 8 athletes had measurable function with the Pelli-Robson chart and 13 with the Mars chart. The remaining athletes had function not numerically measurable by the charts and were considered to have no residual vision. There was no indication that shooting performance varied with visual function, and individuals that had residual vision had no advantage over those without vision for either prone or standing shooting. The modifications made to VI shooting, including the use of auditory tones to guide the gun barrel, appear to have successfully rendered the sport equitable for all eligible athletes. Only one class is necessary for athletes. An improved method of measuring CS in athletes with profound VI would be advantageous.